2011
DOI: 10.1210/en.2011-0031
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor-Initiated Testicular Innate Immune Responses in Mouse Leydig Cells

Abstract: The testis is an immunoprivileged site, where the local cell-initiated testicular innate immune responses play a crucial role in defense against microbial infections. Mechanisms modulating the testicular cell-built defense system remain to be clarified. In this article, we demonstrate that Leydig cells, a major cell population in the testicular interstitium, initiate innate immunity through the activation of Toll-like receptors (TLRs). Several TLRs are expressed in mouse Leydig cells; among these, TLR3 and TLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 45 publications
4
77
0
2
Order By: Relevance
“…These immune cells are thought to constitute the frontline of the epididymal defense against invading microbes (35). Increasing evidence has shown that PRR-initiated innate antimicrobial responses also occur in testicular tissue-specific cells, including Sertoli cells, Leydig cells, and male germ cells (40)(41)(42)(43). The present study demonstrated that the mouse epididymis-specific major cells (i.e., EECs) abundantly express viral sensors TLR3, RIG-I, and DAI.…”
Section: Discussionsupporting
confidence: 51%
“…These immune cells are thought to constitute the frontline of the epididymal defense against invading microbes (35). Increasing evidence has shown that PRR-initiated innate antimicrobial responses also occur in testicular tissue-specific cells, including Sertoli cells, Leydig cells, and male germ cells (40)(41)(42)(43). The present study demonstrated that the mouse epididymis-specific major cells (i.e., EECs) abundantly express viral sensors TLR3, RIG-I, and DAI.…”
Section: Discussionsupporting
confidence: 51%
“…83 We also demonstrated that TAM signaling inhibits the innate immune responses in SCs and Leydig cells. 84,85 Moreover, the Gas6/ProS-TAM system facilitates phagocytic clearance of apoptotic germ cells by SCs. 86 The removal of apoptotic germ cells by phagocytes facilitates the elimination of the auto-antigens, which may reduce endogenous inflammation.…”
Section: Immune Privilege In the Testismentioning
confidence: 99%
“…In addition to SCs, we also found that TLR3 and TLR4 are expressed and are functional in murine Leydig cells. 85 Interestingly, TLR-initiated innate immune responses in Sertoli and Leydig cells are negatively regulated by Gas6/ProS-TAM signaling, which may play roles in avoiding sustained inflammatory conditions that could impair testicular functions. 84,85 Different stages of germ cells also express TLRs.…”
Section: Tlrs In Testicular Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…TYRO3, MER, and AXL are differentially expressed in LCs, Sertoli cells, and testicular macrophages, respectively (47). GAS6 binds to these TAM receptors with markedly different affinities (AXL≥TYRO3>>MER) (2), and GAS6 binds to AXL-Fc, TYRO3-Fc, and MER-Fc at 0.4, 2.7, and 29.0 nM, respectively (48).…”
Section: Figurementioning
confidence: 99%